Perbaikan Kualitas Berkesinambungan dengan Mengintegrasikan Pengembangan Fungsi-fungsi Kualitas dan Metode Taguchi ke Model Six Sigma untuk Kapur Olahan (CaO) - Leksono, Eko Budi (Jurnal Teknik Industri, 2009)
Small Medium Enterprise (SME) such as in Manyar District have 45 furnaces of burning with different capacity. In this area, product quality often not be concerned, many customers are complaint regarding to the its quality which contentration of CaO doesn't meet to user requirement. This research proposed to produce zerro defect and customers satisfaction oriented with integrated quality function deplyoment and taguchi method in six sigma model. This research is done by defining, measuring, improving, and controling stage. By integrating Quality Function Deployment (QFD) and Taguchi into the DMAIC model from six sigma concept obtained: 1) Product quality improvement is accordance with customer need and expectation, 2) More robust for noise, 3) Improved CaO concentration, 4) Quality improvement can be done as sustainable cycle of DMAIC